2002
DOI: 10.1128/jcm.40.11.4211-4217.2002
|View full text |Cite
|
Sign up to set email alerts
|

Optimal DNA Isolation Method for Detection of Bacteria in Clinical Specimens by Broad-Range PCR

Abstract: Broad-range amplification of bacterial DNA from clinical specimens has proved useful for the diagnosis of various bacterial infections, especially during antimicrobial treatment of the patient. Optimal sample processing protocols for diagnostic broad-range bacterial PCR should release DNA from an array of target organisms with equal efficiencies and wash out inhibitory factors from various sample types without introducing bacterial DNA contamination to the amplification reaction. In the present study, two phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 11 publications
2
101
2
1
Order By: Relevance
“…The coupled efficiency of two methods for RNA quantification, PCR and spectrophotometry, was also determined. Physical cell wall disintegration by sonication was previously described for RNA isolation in organisms with difficult-to-lyse cell walls (Frostegard et al, 1999;Rantakokko-Jalava et al, 2002), but in the present study, this method was not effective for isolating SP RNA. Enzymatic digestion by mutanolysin treatment or mutanolysin combined with proteinase K and SDS was also reported to yield high quality RNA and DNA from gram positive bacteria (Ampe et al, 1998;Fliss et al, 1991;Gopalakrishna et al, 1981;Shiroza et al, 1998;Simpson et al, 1993;Zhou et al, 1996), but again, the present study documented only a low RNA yield for these procedures and suggested that the required sample incubations at 50 o C ~ 37 o C may have been responsible by causing significant RNA degradation.…”
Section: Discussioncontrasting
confidence: 49%
“…The coupled efficiency of two methods for RNA quantification, PCR and spectrophotometry, was also determined. Physical cell wall disintegration by sonication was previously described for RNA isolation in organisms with difficult-to-lyse cell walls (Frostegard et al, 1999;Rantakokko-Jalava et al, 2002), but in the present study, this method was not effective for isolating SP RNA. Enzymatic digestion by mutanolysin treatment or mutanolysin combined with proteinase K and SDS was also reported to yield high quality RNA and DNA from gram positive bacteria (Ampe et al, 1998;Fliss et al, 1991;Gopalakrishna et al, 1981;Shiroza et al, 1998;Simpson et al, 1993;Zhou et al, 1996), but again, the present study documented only a low RNA yield for these procedures and suggested that the required sample incubations at 50 o C ~ 37 o C may have been responsible by causing significant RNA degradation.…”
Section: Discussioncontrasting
confidence: 49%
“…P2 and P3 protocols had high-purity products (A260/A280 1.81 and 1.92, respectively). This may be due to the use of high concentration of lysozyme (50 mg/mL) for P2 protocol and the additional step of protein precipitation and RNase (20 mg/mL) for P3 protocol, which may have resulted in the removal of contaminants and increased the purity, similar to the previously described investigations (10,21). The purity of DNA in all kit-based protocols was ~1.50 which was lower than that of the traditional protocols.…”
Section: Discussionmentioning
confidence: 63%
“…2). This work demonstrated that molecular detection of bacteria with resistant cell walls in clinical samples could be enhanced by the use of physical cell wall desintegration methods as related by others authors (Rantakokko-Jalava and Jalava, 2002). Results also indicated that no single method was optimal for the detection of all bacteria that might be present in biological fluids, and the use of more than one method should be recommended.…”
Section: Resultsmentioning
confidence: 82%
“…The cell wall of Gram-positive bacteria can be broken by the use of enzymes that degrade peptidoglycans such as the lysozyme and mutanolysin present in the commercial kits (Yano et al, 2002;Old et al, 2006), which cause the method to be expensive. The use of cheaper alternative methods is not always appropriated given the difficulty in breaking the cell wall when some reagents are used, such as phenol-ether (Rantakokko-Jalava and Jalava, 2002). In this sense, bacterial DNA can be extracted from sera by boiling without using any toxic reagent, overcoming the use of expensive commercial kits for DNA purification (Mayoral et al, 2005).…”
Section: Introductionmentioning
confidence: 99%